2003
DOI: 10.1007/s00234-002-0887-7
|View full text |Cite
|
Sign up to set email alerts
|

Cortical laminar necrosis in brain infarcts: serial MRI

Abstract: High-signal cortical lesions are observed on T1-weighted images in cases of brain infarct. Histological examination has demonstrated these to be "cortical laminar necrosis", without haemorrhage or calcification. We report serial MRI in this condition in 12 patients with brain infarcts. We looked at high-signal lesions on T1-weighted images, chronological changes in signal intensity and contrast enhancement. High-signal cortical lesions began to appear about 2 weeks after the ictus, were prominent at 1-2 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 7 publications
6
74
2
1
Order By: Relevance
“…Serial imaging studies of laminar necrosis by using CT and T2*-weighted images showed no hemorrhage. 12,20 In the present study, no increase of hemorrhage or subsequent hematoma was found in the laminar necrosis on follow-up examination. Thus, hemorrhage in the laminar necrosis, if present, may involve a limited area and should not be considered as related to subsequent hematoma.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Serial imaging studies of laminar necrosis by using CT and T2*-weighted images showed no hemorrhage. 12,20 In the present study, no increase of hemorrhage or subsequent hematoma was found in the laminar necrosis on follow-up examination. Thus, hemorrhage in the laminar necrosis, if present, may involve a limited area and should not be considered as related to subsequent hematoma.…”
Section: Discussioncontrasting
confidence: 49%
“…12,20 Kashihara et al 21 reported that cortical laminar necrosis was observed in a patient with central nervous system lupus erythematosus for 5 years. Serial imaging studies of laminar necrosis by using CT and T2*-weighted images showed no hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…5 Early gyral contrast enhancement as seen in our case could be related to the severity of hypoxic brain damage leading to breakdown of blood brain barrier and reperfusion of the hypoxic ischemic brain. Overall, our case depicts MRI findings of HIBI in an adult patient as described in literature.…”
Section: Discussionmentioning
confidence: 49%
“…Cortical laminar necrosis presents as a band of necrosis in the cortex at histological examination, and is a specific pattern of ischemic injury to the neurons in the cortex. 1,2,7,16,17) Within the cortex, the third layer is the most vulnerable, followed by the fifth and sixth, with the second and fourth being relatively more resistant to ischemic necrosis from hypoperfusion. 5) Cortical laminar necrosis appears as hyperintense lesions with a laminar pattern on T 1 -weighted MR imaging, without signs of hemorrhage or calcification on T 2 * -weighted MR imaging or CT. 4,6,9,12,13) Histological examination shows neuronal damage and reactive tissue change with reactive gliosis and fat-laden macrophages resulting in protein degradation.…”
Section: Discussionmentioning
confidence: 99%